2012
DOI: 10.1038/nmat3222
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic mast-cell granules as adjuvants to promote and polarize immunity in lymph nodes

Abstract: Granules of mast cells (MCs) enhance adaptive immunity when, on activation, they are released as stable particles. Here we show that submicrometre particles modelled after MC granules augment immunity when used as adjuvants in vaccines. The synthetic particles, which consist of a carbohydrate backbone with encapsulated inflammatory mediators such as tumour necrosis factor, replicate attributes of MCs in vivo including the targeting of draining lymph nodes and the timed release of the encapsulated mediators. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…17 Recently, PECs prepared from natural macromolecules have attracted attention for use in the development of drug-delivery systems, such as the complex between Cs and heparin, which have been formulated as vaccine adjuvants. 18 Some studies have investigated the drug-delivery systems based on Cs-ChS complexes, such as Huang et al, 19 Ganza-Gonzáles et al, 20 and Sui et al, 21 who have reported the use of Cs-ChS-based microcapsules for controlled release by 5-fluorouracyl, heparin, and metoclopramide, respectively, in their studies. Yeh et al characterized protein-loaded Cs-ChS nanoparticles using the PEC technique, 22 while Hu et al studied the influence of charge on fluorescein isothiocyanate (FITC)-bovine serum albuminloaded Cs-ChS nanoparticles upon cell uptake in human Caco-2 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, PECs prepared from natural macromolecules have attracted attention for use in the development of drug-delivery systems, such as the complex between Cs and heparin, which have been formulated as vaccine adjuvants. 18 Some studies have investigated the drug-delivery systems based on Cs-ChS complexes, such as Huang et al, 19 Ganza-Gonzáles et al, 20 and Sui et al, 21 who have reported the use of Cs-ChS-based microcapsules for controlled release by 5-fluorouracyl, heparin, and metoclopramide, respectively, in their studies. Yeh et al characterized protein-loaded Cs-ChS nanoparticles using the PEC technique, 22 while Hu et al studied the influence of charge on fluorescein isothiocyanate (FITC)-bovine serum albuminloaded Cs-ChS nanoparticles upon cell uptake in human Caco-2 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…In an elegant biomimetic strategy, St. John et al (89) packaged inflammatory cytokines (TNF-α or IL-12) in polyelectrolyte NPs mimicking mast cell granules (Figure 3). These synthetic granules were engineered by complexing heparin (the key cytokine-binding component of native mast cell granules) and chitosan together with cytokine cargos (Figure 3 a and b ); these granules effectively targeted minute quantities of cytokines to LNs following injection (Figure 3 c ).…”
Section: Effects Of Biomaterials On Immune Cells and Immunomodulamentioning
confidence: 99%
“…Combinations of transforming growth factor (TGF)-β1, IL-2, and either rapamycin (104) or retinoic acid (89) have been shown to induce a Treg phenotype, and to suppress naive T cell proliferation and function, and are capable of inducing Foxp3 + Tregs in human cells. Both rapamycin and retinoic acid have been found to produce Tregs with similar functionality but with drastically different expression levels of CCR7, CCR9, and CCR10 (105), leading to significantly different migratory patterns and distributions in vivo (104).…”
Section: Effects Of Biomaterials On Immune Cells and Immunomodulamentioning
confidence: 99%
See 1 more Smart Citation
“…TNF contained within these granules leads to lymph node enlargement, indicating that it is involved in initiation of immune responses. Interestingly, coadministration of synthetic particles that contain TNF to mimic mast cell granules improves the efficacy of vaccination against influenza infection (St John et al, 2012).…”
Section: Figure 2 Mast Cell Interactions With Influenza Virus Producmentioning
confidence: 99%